Factor associated with alcohol use among Lahu and Akha hill tribe youths, northern Thailand - Onnalin Singkorn; Tawatchai Apidechkul; Bukhari Putsa; Sudkhed Detpetukyon; Rachanee Sunsern; Phitnaree Thutsanti; Ratipark Tamornpark; Panupong Upala; Chadaporn Inta (BMC, 2019)
Abstract Background Alcohol use impacts several dimensions, including physical health, mental health, families, and social interactions. This study aimed to estimate the prevalence and to determine the factors associated with alcohol use among Akha and Lahu hill tribe youths in Chiang Rai, Thailand. Methods An analytic cross-sectional design was applied to obtain key data on these associations. The study sample was Akha and Lahu hill tribe youths aged 15-24 years who lived in 30 selected hill tribe villages. A questionnaire was developed from an in-depth interview and group discussion and tested for validation and reliability before use. Descriptive statistics were used to demonstrate the general characteristics, and Chi-square test and logistic regression were used to detect associations between variables at α=0.05. Results A total of 737 subjects were recruited into the study, of whom 50.0% were Lahu. The average age was 17.9 years, 80.7% were single, 71.1% were Christian, 65.9% graduated secondary school, and 65.7% had their major source of income from their parents. Overall, 17.3% smoked and 45.0% drank alcohol. Among the drinkers, 79.8% drank beer, 61.5% started drinking at an age of 15-19 years, 86.8% had drank for < 5 years, 42.5% were persuaded to drink by their peers, 20.2% suffered an accident after alcohol use, and 17.2% had experienced unsafe sex after drinking alcohol. In the multiple logistic regression, six variables were associated with alcohol use among the Akha and Lahu youths. Males had greater odds of alcohol use than females (ORadj = 3.50, 95% CI = 2.24-5.47). Buddhists had greater odds of alcohol use than Christians (ORadj = 1.88, 95% CI = 1.17-3.04). Participants who were unemployed, employed, and in other categories of occupation had greater odds of alcohol use than those who were students (ORadj = 2.20, 95% CI = 1.23-3.92; ORadj = 6.89, 95% CI = 3.38-13.89; and ORadj = 2.96, 95% CI = 1.01-8.59, respectively). Participants whose fathers were daily wage workers had greater odds of alcohol use (ORadj = 2.89; 95% CI = 1.23-6.79) than those whose parents worked in agriculture, and those whose fathers used alcohol had greater odds of alcohol use than those whose fathers did not use alcohol (ORadj = 2.17, 95% CI = 1.40-3.35). Finally, those who had 6-10 and ≥ 11 close friends living in the same village who used alcohol had greater odds of alcohol use (ORadj = 8.51, 95% CI = 3.10-23.3; and ORadj = 3.84, 95% CI = 1.15-12.77, respectively). Conclusion To reduce the initiation of alcohol use among Akha and Lahu youths, public health intervention programs should focus on males who are not attending school and should be implemented for both their family members and peers.